Indenoannulated tridecacyclene: an all-carbon seven-stage redox-amphoter - Misselwitz, Erik; Spengler, Jonas; Rominger, Frank; Kivala, Milan (Chemistry - a European journal, 2024)
We disclose an indenoannulated tridecacyclene comprising a central cyclooctatetraene moiety with multiple adjacent pentagonal rings which is accessible in a concise synthetic sequence. The saddle-shaped geometry of the non-benzenoid polycyclic scaffold and its unique packing behavior in the solid state were characterized by X-ray crystallography. In electrochemical studies, the compound undergoes seven reversible redox events comprising five reductions and two oxidations. The dicationic and dianionic species obtained by chemical oxidation and reduction, respectively, were characterized spectroscopically in solution. Density functional theory calculations were applied to provide insights into aromaticity evolution in the respective charged species, highlighting the beneficial effect of the non-benzenoid moieties on charge stabilization
Online verfügbar: 02. April 2024
Gesehen am 31.07.2024